Design of a high accuracy wideband current sensing system by tunneling magnetoresistive device with digital parametric equalizer - Sen Qian; Hui Huang; Fuchao Li; Qiang Shi; Xiaohui Yan; Jinghong Guo (Sensors International)
Wideband current sensors play a crucial role in the future power grid, especially with the increasing integration of renewable energy and nonlinear loads. This research developed a sensor configuration using tunneling magnetoresistive (TMR) devices for wideband current measurement. A parametric equalizer was also introduced to compensate for minor fluctuations in the TMR sensor's frequency response, thereby reducing wideband measurement errors. A calibration setup was created to test the frequency-dependent accuracy of the compensated TMR sensor. Results showed that relative errors in wideband measurements were reduced to 2 % after compensation, compared to 6 % of the uncompensated results, with power frequency measurement errors falling below 1 %. Furthermore, the designed TMR sensors were deployed in a 0.4 kV household district, demonstrating their practical application in diagnosing the spectral content of the load current. The analysis revealed a range of wideband components, including low-frequency components below 50 Hz, intermediate harmonics, and supraharmonics.